Memantine and reduced time with dyskinesia in Parkinson′s Disease. (3rd August 2015) - Wictorin, K.; Widner, H.
Abstract : Objectives: The partial glutamate antagonist amantadine is currently used in clinical practice, to reduce dyskinesia developing as a side‐effect of levodopa treatment in patients suffering from Parkinson's disease (PD). This study was aimed at evaluating the antidyskinetic effect of another glutamate antagonist, memantine. Methods and materials: We performed a randomized, double‐blind and placebo‐controlled crossover clinical trial of memantine (20 mg), with a 3‐week treatment period, and 15 patients completed the study. Results: The primary outcome measure, a change in observed dyskinesia ratings, did not reach significance. Seven of the 15 patients reduced the L‐dopa‐induced dyskinesias by 32%, whereas for three patients, they increased by 33%, and for five patients, they did not change. Data from the self‐administered diaries, as a secondary outcome measure, did show a significant 35% reduction in the percentage of time of the day spent with dyskinesia, from 25% (placebo) to 16% (memantine). Memantine was well tolerated, without any serious adverse events, or worsening in the parkinsonian motor score. Conclusion: The results suggest that memantine may be a useful antidyskinetic drug, and a larger clinical study is warranted.